How much do college students with ADHD benefit from retrieval practice when learning key-term definitions?. (August 2020) - Knouse, Laura E.; Rawson, Katherine A.; Dunlosky, John
Abstract: Undergraduate students with ADHD may benefit from retrieval practice but may have difficulty using this strategy consistently. We examined whether undergraduates with ADHD benefit as much as non-ADHD students from self-regulated retrieval practice and retrieval practice to criterion. Students with ADHD ( n  = 58) and without ( n  = 121) learned key term definitions by studying, practicing retrieval, and judging the accuracy of their responses using a computer interface. One group self regulated their learning; the other learned items to criterion of three correct retrievals. After one week, recall and recognition were as high for students with ADHD as those without ADHD, regardless of whether students regulated their learning or were forced to achieve criterion. Among those who regulated their learning, students with and without ADHD used retrieval practice and feedback to a similar degree. Results support recommending retrieval practice to criterion for college students with and without ADHD. Highlights: Compared self-regulation of retrieval practice in students with and without ADHD. Benefits of retrieval practice did not depend on ADHD status. Students with ADHD self regulated retrieval practice similarly to non-ADHD students. The computer interface used in the study may have scaffolded retrieval practice. Results support recommending retrieval practice to criterion to college students with ADHD.